2016
DOI: 10.3892/mmr.2016.4810
|View full text |Cite
|
Sign up to set email alerts
|

Chronic sciatic nerve compression induces fibrosis in dorsal root ganglia

Abstract: In the present study, pathological alterations in neurons of the dorsal root ganglia (DRG) were investigated in a rat model of chronic sciatic nerve compression. The rat model of chronic sciatic nerve compression was established by placing a 1 cm Silastic tube around the right sciatic nerve. Histological examination was performed via Masson's trichrome staining. DRG injury was assessed using Fluoro Ruby (FR) or Fluoro Gold (FG). The expression levels of target genes were examined using reverse transcription-qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Moreover, compression of the sciatic nerve in rats induced fibrosis near the lesions and the ipsilateral dorsal root ganglion. This occurred 3 weeks after the compression using the Silastic tube [25].…”
Section: Genetics and Vitamin Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, compression of the sciatic nerve in rats induced fibrosis near the lesions and the ipsilateral dorsal root ganglion. This occurred 3 weeks after the compression using the Silastic tube [25].…”
Section: Genetics and Vitamin Dmentioning
confidence: 99%
“…They found the cicatrix formed after the injury may sensitize the dominant nerve in the dorsal root ganglia [24]. Li et al [25] in 2016 studied the effects of compression of the sciatic nerve in rats to investigate the pathological alterations in the neurons of the dorsal root ganglia [25]. They reported at 3 weeks after the compression, collagen fibers accumulated around the compressed sciatic nerve, and at 8 weeks, excessive collagen formation with muscle atrophy was observed [25].…”
Section: The Role Of Vitamin D In the Etiopathogenesis Of Adolescent mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies (Lv et al., ; Wang, Hurwitz, et al., ) have shown that Tau is more sensitive in neuronal ischemic injury after molecular markers. In the vascular dementia rat model, Tau expression was significantly increased, and neuronal apoptosis occurred simultaneously, suggesting the function of Tau phosphorylation in initiating cellular apoptosis (Li, Chen, Chen, Cong, & Chen, ). In our study, we found that vGlut3, a glutamate transporter that is closely related to PSD‐95, was significantly decreased in the rat DRG after sustained compression of DRG.…”
Section: Discussionmentioning
confidence: 99%
“…Three SD rats were used for retrograde tracing of Fluor-Gold (FG; Fluorochrome; 80014; Sigma-Aldrich, St. Louis, MO) as previously described (Li et al, 2016). The modified procedure was as follows: A glass micropipette (tip diameter 40–60 μm) connected to a microsyringe (1 μl, Hamilton, Reno, NV, United States) was inserted into the epineurium 2 mm from the distal point of the injured site of the sciatic nerve.…”
Section: Methodsmentioning
confidence: 99%